OPTIMIZATION OF SILKSCREEN PRINTING PARAMETERS TO IMPROVE THE QUALITY OF DECORATIVE ELEMENTS IN WOMEN'S CLOTHING (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The article deals with the issue of optimizing the parameters of silkscreen printing in order to improve the quality of decorative elements in women's clothing. In the course of the study, the influence of the angle of inclination of the squeegee, the pressure force and the thickness of the paint layer on the quality of a decorative printed pattern was experimentally studied. As a result of experiments, it was found that with a squeegee tilt angle of 75-80°, a pressure of 0.4–0.6 MPa and an ink layer thickness of 120-150 microns, the highest print quality indicators are achieved. Based on the obtained data, practical recommendations for industrial applications are developed.